STRENGTHENING RELIGIOUS MODERATION AT UIN SUNAN GUNUNG DJATI BANDUNG: STUDY AT RELIGIOUS MODERATION HOUSE - Zulkarnain Yani (Penamas, 2022)
The issue of religious moderation is one of the main issues in the strategic plan of the Ministry of Religious Affairs for more moderate religious communities. Therefore, in 2019, the Ministry of Religious Affairs of the Republic of Indonesia declared 2019 as the Year of Religious Moderation, in that year, the Ministry of Religion through the Director-General of Islamic Education issued a Circular of the Director-General of Islamic Education regarding the Circular of Religious Moderation Houses within State Islamic Religious Universities. UIN Sunan Gunung Djati Bandung immediately implemented the circular by establishing Rumah Moderasi Beragama. The existence of Rumah Moderasi Beragama in order to strengthen religious moderation and convey messages of peace and tolerance in carrying out daily religious teachings for lecturers and students. This paper will examine how the strengthening of religious moderation is carried out by Rumah Moderasi Beragama and evaluate the implementation of religious moderation. So that it will be known how Rumah Moderasi Beragama of UIN Sunan Gunung Djati Bandung implements strengthening the understanding of religious moderation and its relation to policies from the Ministry of Religious Affairs regarding religious moderation programs in universities. This research uses a qualitative-descriptive approach with a case study of the Moderation House by conducting a study of the products of Rumah Moderasi Beragama in the implementation of activities on campus. Based on the results in the field, Rumah Moderasi Beragama of UIN Sunan Gunung Djati Bandung in the implementation of strengthening religious moderation published five modules that were used in the implementation of activities and programmatically carried out various activities in accordance with the Ministry of Religious Affairs policy in strengthening religious moderation in university.